2014
DOI: 10.1186/1742-4755-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Practices and determinants of delivery by skilled birth attendants in Bangladesh

Abstract: Introduction: Utilization of Skilled Birth Attendants (SBAs) at birth is low (20%) in Bangladesh. Birth attendance by SBAs is considered as the "single most important factor in preventing maternal deaths". This paper examined the practices and determinants of delivery by SBAs in rural Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 24 publications
20
31
0
Order By: Relevance
“…The finding of our study that education level of the women and their husbands had association with delivery attendance is supported by other studies (8,9,11). The educated couples might be more aware of the importance of skilled attendance during delivery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding of our study that education level of the women and their husbands had association with delivery attendance is supported by other studies (8,9,11). The educated couples might be more aware of the importance of skilled attendance during delivery.…”
Section: Discussionsupporting
confidence: 91%
“…Women who received antenatal check-up from a skilled provider were more likely to be delivered by skilled attendants than the women who were not checked by a skilled health care provider. Other studies also found a similar association (8,9,11,12). The increased likelihood of skilled attendance could have an association with receiving information and counseling from the health care providers regarding the importance of safe delivery attendance during that period.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Earlier studies that examined factors associated with care seeking found that women belonging to wealthier households were more likely to seek skilled care for antepartum complications [11, 13]. Factors associated with skilled birth attendants during intrapartum period included mothers’ occupation, higher parity, complications during antepartum period, having antenatal care [14], and closer distance to a health facility [13, 15, 16]. In addition, access to skilled attendants, availability of quality care and associated medical cost remained major barriers to seeking care [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the number of nurses and midwives is falling sharply; the latest data found in 2011 was 0.22 in per 1000 people [1]. Approximately 3 million births take place yearly in Bangladesh and a 20% rise of institutional delivery means that at least an extra 600,000 deliveries need to be conducted at the health facilities [24]. In general, the present health facilities in Bangladesh are not ready to handle these large numbers of deliveries with SBAs.…”
Section: Human Resourcesmentioning
confidence: 99%